Oviposition Strategies in Beneficial Insects. (24th July 2018) - Riddick, Eric W; Dindo, Maria Luisa; Grodowitz, Michael J; Cottrell, Ted E
AIMS AND SCOPE: The aim of this special collection is to highlight the importance of reproduction (ie, oviposition) in the life history, population dynamics, survival, and fitness of beneficial insects, broadly defined. Specific areas of interest include the (1) identification of natural products to boost oviposition; (2) importance of chemical cues in oviposition site selection; (3) influence of host plant defenses on oviposition success; (4) reproductive physiology and the frequency of egg laying; (5) trade-offs between maternal size and egg size; (6) foraging behavior, host selection, and oviposition in parasitoids; and (7) oviposition decisions in the face of intraguild predators.